Transcriptome profiling of Hibiscus sabdariffa L. at two maturation stages of calyx tissue - Hamzah, Nur Atheeqah (2020)
Roselle (Hibiscus sabdariffa L.) is a non-model plant species whose calyces have been studied progressively in science for their metabolite composition and pharmacological potentials in the treatment of hypertension, diabetes, cancer, hyperlipidemia and hyperglycemia. The genetic mechanism that governs the production of potent phytochemicals found in roselle calyx tissues such as anthocyanin are yet to be deciphered and understood. The purpose of this study is to construct a transcriptome dataset for H. sabdariffa calyx tissues during the last two stages of maturation (stages three and four) using next-generation sequencing (NGS) technologies. These two maturation stages are critical as they may affect the quality of the calyx produced. A series of wet lab experiments were conducted prior to sequencing which included RNAextractions, rRNA-depletion and cDNA sequencing library constructions. The Illumina NextSeq 500 sequencer platform was employed for sequencing; while data analysis was orchestrated using a number of software that included Trinity version 2.2.0 and CLC Genomic Workbench version 10.1.0. A combined total of more than 200 million good quality paired-end reads were generated from sequencing that resulted in a de novo assembled reference transcriptome consisting of 221,334 transcripts, of which 92,974 transcripts (42%) were successfully annotated. Twelve anthocyanin-related genes were effectually annotated; chalcone synthase, chalcone isomerase, flavanone 3-hydroxylase, flavanoid 3’-monoxygenase, flavonoid 3’,5’-hydroxylase, dihydroflavonol 4-reductase, leucoanthocyanidin dioxygenase, flavonoid 3-O-glucosyltransferase, anthocyanidin 3- O-glucoside 2''-O-glucosyltransferase, coumaroyl-CoA:anthocyanidin 3-O-glucoside- 6''-O-coumaroyltransferase, malonyl-CoA:anthocyanidin 5-O-glucoside-6''-Omalonyltransferase and flavonoid 3',5'-methyltransferase in this dataset. Differential expression analysis had identified a total of 504 significant differentially expressed genes (SDEGs) that were effectively mapped onto 193 KEGG pathway maps. The secondary metabolites biosynthesis category had attained a relatively high number of SDEGs (40) mappings. To name a few: the phenylalanine biosynthesis pathway, isoquinoline alkaloid biosynthesis pathway, diterpenoid biosynthesis pathway, and stilbenoid, diarylheptanoid and gingerol biosynthesis pathway. This study represents the first time the transcriptome of H. sabdariffa calyx tissues were sequenced using NGS technologies. The novel transcriptomic data produced in this research provides an expansion of information on the genetics alongside their dynamics in the calyx tissues of H. sabdariffa throughout the third and fourth maturation stages, which is useful for future studies on functional analysis and marker development.